Danhong Huayu Koufuye Prevents Diabetic Retinopathy in Streptozotocin-Induced Diabetic Rats via Antioxidation and Anti-Inflammation - Wenpei Chen; Xiaolan Yao; Chenghao Zhou; Ziyang Zhang; Gang Gui; Baoqin Lin (Hindawi Limited, 2017)
Danhong Huayu Koufuye (DHK), a traditional Chinese prescription, is used to treat central retinal vein occlusion clinically. We previously reported that DHK prevented diabetic retinopathy (DR) in rats. Moreover, we found that it protected endothelial cells from hyperglycemia-induced apoptosis through antioxidation and anti-inflammation. Here, we investigated whether antioxidative and anti-inflammatory activities of DHK contributed to its therapeutic effect on DR in streptozotocin- (STZ-) induced diabetic rats. DHK significantly blocked the breakdown of the blood-retinal barrier (BRB) and increased the thickness of the inner nuclear layer (INL), as well as suppressed the swelling of the ganglion cell layer (GCL) in diabetic retinas. DHK remarkably increased the activities of superoxide dismutase (SOD) and glutathione peroxidase (GPx) in plasma, and decreased serum level of nitric oxide (NO). Moreover, DHK markedly reduced the serum levels of vascular endothelial growth factor (VEGF) and intercellular adhesion molecule-1 (ICAM-1). Furthermore, DHK significantly downregulated protein expressions of VEGF and inducible NO synthase (iNOS) and mRNA expression of ICAM-1 in retinas. These results suggest that the antioxidative and anti-inflammatory activities of DHK may be important mechanisms involved in the protective effect of DHK on DR in STZ-induced diabetic rats.